Odpowiedzi

2010-03-20T17:56:40+01:00
A) 1/2 x - 3/4 [ x - (4x +1)] = 1 -( x+ 1) / 4 / mnożymy obustronnie przez 4
2x - 3(x-4x-1)=4-(x+1)
2x-3(-3x-1)=4-x-1
2x+9x+3=3-x
11x+3=3-x
12x+3=3
12x=0
x=0

b) 2/3 (3x - 1) - 3/2 [2x + 3(x -2) ] =1 /mnożymy obustronnie przez 6
4(3x-1) - 9(2x+3x-6)=6
12x-4-45x+54=6
-33x+50=6
33x=44
3x=4
x=4/3
6 4 6
2010-03-20T18:01:54+01:00
A) 1/2x- 3/4 [x-(4x+1 )]= 1 - x+1/4
a) 1/2 x - 3/4 [ x - (4x +1)] = 1 -( x+ 1) / *4
2x - 3(x-4x-1)=4-(x+1)
2x-3(-3x-1)=4-x-1
2x+9x+3=3-x
11x+3=3-x
12x+3=3
12x=0/:12
x=0


b)b) 2/3 (3x - 1) - 3/2 [2x + 3(x -2) ] =1/*6
4(3x-1) - 9(2x+3x-6)=6
12x-4-45x+54=6
-33x+50=6
33x=44
3x=4/:3
x=4/3
3 4 3
Najlepsza Odpowiedź!
2010-03-20T18:04:09+01:00
A) 1/2x - 3/4 [x - (4x +1)] = 1 -(x+ 1) / *4
2x - 3(x-4x-1)=4-(x+1)
2x-3(-3x-1)=4-x-1
2x+9x+x=3-3
12x=0 / : 12
x=0


b) 2/3(3x-1) - 3/2[2x+3(x-2)] =1 / * 6
4(3x - 1) - 9[2x+3(x-2)] = 6
12x - 4 - 9[2x + 3x - 6] = 6
12x - 4 - 18x - 27x + 54 = 6
12x - 18x - 27x = 6 + 4 - 54
-33x = -44 / *(-1)
33x = 44 / : 11
3x = 4 /: 3
x = 4/3
5 4 5